2013
DOI: 10.4161/rna.26500
|View full text |Cite
|
Sign up to set email alerts
|

Structure and RNA-binding properties of the Type III-A CRISPR-associated protein Csm3

Abstract: The prokaryotic adaptive immune system is based on the incorporation of genome fragments of invading viral genetic elements into clusters of regulatory interspaced short palindromic repeats (CRISPRs). The CRISPR loci are transcribed and processed into crRNAs, which are then used to target the invading nucleic acid for degradation. The large family of CRISPR-associated (Cas) proteins mediates this interference response. We have characterized Methanopyrus kandleri Csm3, a protein of the type III-A CRISPR-Cas com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 45 publications
6
41
0
Order By: Relevance
“…The cross-linking sites within T. pendens Cas7 encircle a positively charged groove and biochemical analysis demonstrated that conserved residues in this groove contribute significantly to RNA binding [24]. Moreover, the location of the cross-linked residues within the predicted insertion domain 1 of the proteins T. tenax Cas7 and T. thermophilus Csm3 are in full agreement with previous studies on the respective Type I-A and III-A homologs, Sulfolobus solfataricus Cas7 and Methanopyrus kandleri Csm3 [23,52].…”
Section: Cross-link Sites On the Structural Model Of Cas7 Proteinssupporting
confidence: 88%
See 2 more Smart Citations
“…The cross-linking sites within T. pendens Cas7 encircle a positively charged groove and biochemical analysis demonstrated that conserved residues in this groove contribute significantly to RNA binding [24]. Moreover, the location of the cross-linked residues within the predicted insertion domain 1 of the proteins T. tenax Cas7 and T. thermophilus Csm3 are in full agreement with previous studies on the respective Type I-A and III-A homologs, Sulfolobus solfataricus Cas7 and Methanopyrus kandleri Csm3 [23,52].…”
Section: Cross-link Sites On the Structural Model Of Cas7 Proteinssupporting
confidence: 88%
“…In vivo, several copies of Cas7 proteins are wrapped around crRNA in a sequence-unspecific helical fashion [5,30,50,51]. Crystal structures from single and complex-bound Cas7 proteins show two composite RNA-binding surfaces: a central cleft and a structurally variable insertion domain [5,23,24,52]. In all Cas7 proteins characterized to date both these domains are defined by insertions within the secondary structure elements of the central RRM domain (insertion domain 1 is b1-a1, b2-b3, a2-b4, and insertion domain 2 is a1-b2).…”
Section: Mapping the Rna Binding Interface In Cas7 Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these flanking elements, Cmr4 has a rather elongated structure (about 60 3 25 Å ), with an extended b sheet effectively sandwiched between two layers of a helices. Structural comparison with Mk Csm3 (Hrle et al, 2013), the putative Cmr4-like subunit in type III-A effector complexes, shows large differences in the structural elements that sandwich the central b sheet.…”
Section: Cmr4 and Cmr5 Assemble Into Backbone-like Superhelical Strucmentioning
confidence: 99%
“…Interestingly, not only is Pf D26 Cmr4 conserved in Cmr orthologs from type III-B systems ( Figures 5D and S4A), but it is also one of the few amino acid residues to be conserved in the Csm3 proteins (e.g., Mk D35 Csm3 ; Hrle et al, 2013), the putative backbone protein in type III-A systems (Figures 5D and S4B). …”
Section: The Nuclease Active Site Of the Cmr Complex Resides In Cmr4mentioning
confidence: 99%